2019
DOI: 10.1126/scitranslmed.aat3356
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of circulating TNF during adalimumab treatment using a drug-tolerant TNF assay

Abstract: Patients with rheumatoid arthritis (RA) can be successfully treated with tumor necrosis factor (TNF) inhibitors, including the monoclonal antibody adalimumab. Once in remission, a proportion of patients can successfully discontinue treatment, indicating that blocking TNF is no longer required for disease control. To explore the dynamics of circulating TNF during adalimumab treatment, we developed a competition enzyme-linked immunosorbent assay that can quantify TNF in the presence of large amounts of TNF inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 40 publications
4
51
2
Order By: Relevance
“…This is in line with what has been found for adalimumab treatment. However, TNF concentrations measured in this study were at least twice as low as TNF concentrations during adalimumab treatment (1). The high baseline TNF concentrations in 25% of the patients were also surprising, as it indicates that patients switch to golimumab while their TNF is still in complex with a previous TNF-inhibitor.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…This is in line with what has been found for adalimumab treatment. However, TNF concentrations measured in this study were at least twice as low as TNF concentrations during adalimumab treatment (1). The high baseline TNF concentrations in 25% of the patients were also surprising, as it indicates that patients switch to golimumab while their TNF is still in complex with a previous TNF-inhibitor.…”
mentioning
confidence: 57%
“…Berkhout et al (2019) described the development of a novel drug-tolerant assay to quantify TNF during TNFinhibitor treatment. Using this assay, they analyzed the dynamics of TNF during treatment of rheumatoid arthritis (RA) patients with adalimumab and found that TNF levels shortly after treatment initiation predict nonresponse (1).…”
mentioning
confidence: 99%
“…The prevalence of clustered ADRs between the various bDMARDs was compared using a c 2test and the average burden was compared using a Mann-Whitney U test. Results: In the Dutch Biologic Monitor 583 consecutive (44.8%) RA patients were included (71.2% female, average age 59 years, SD±12.4) using the originator or a biosimilar of etanercept (ETN, 265), adalimumab (ADA,196), tocilizumab (41), abatacept (35), certolizumab pegol (23), rituximab (19), infliximab (18), golimumab (15), sarilumab (2), secukinumab (1), anakinra (1)…”
Section: Fri0097mentioning
confidence: 99%
“…Background: Golimumab is a monoclonal antibody that binds TNF, counteracting its pro-inflammatory effects. Berkhout et al (2019) described the development of a novel drug-tolerant assay to quantify TNF during TNFinhibitor treatment. Using this assay, they analyzed the dynamics of TNF during treatment of rheumatoid arthritis (RA) patients with adalimumab and found that TNF levels shortly after treatment initiation predict nonresponse (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation